Դավիթ Անանունի «Անցյալի մեծարանքը» - Մնացականյան, Ե. (ՀՀ ԳԱԱ հրատ.)
The article focuses on the “The Esteem of the Past” by D. Ananun, its basic theses and the important points in the discussions around them. The debates are centered around the question whether Toumanyan attempts to idealize the village life or not. The answer directly comes from one of the poet's beliefs concerning the content of aesthetic ideal. For the first time, all the articles, response letters and critical reviews are collected. H. Oshakan, Tz. Khanzadyan, H. Sourkhanyan, S. Hakobyan and other critics speak from different angles. The opposing sides, bringing to life valuable points, stay in extreem positions and do not notice the genius of Toumanyan's composition. В статье представлены основные положения исследования «Дань прошлому» Давида Анануна и основные концепции дискуссий, развернутых вокруг них. В основе дискуссии затрагивается основной вопрос: идеализирует ли Туманян мир армянского крестьянства или нет? Ответ прямо соотносится с одним из основных сторон мировоззрения поэта – содержанием эстетического идеала. Впервые выделяются и обобщаются почти все статьи-отзывы и рецензии. С разных точек зрения выступают критики О. Ошакан, Ц. Ханзадян. О. Сурхатян, С. Акопян и другие. Оппоненты, выдвигая ценные точки зрения, остаются на крайних позициях, не замечая важнейшие свойства творчества Туманяна.
Keywords: Գրականություն